Lived Experiences of Patients Following Myocardial Infarction Diagnosis in an Impoverished region in Pakistan‒A Qualitative Study - Noor, Amtul; Haiy, Ata Ul; Sami, Amtul; Masudul Hasan Nuri, Muhammad (International Journal of Medical Students, 2025)
BACKGROUND: Cardiovascular disease (CVD) is a leading cause of death worldwide, accounting for 19 million deaths in 2020 alone. Ischemic heart disease being the leading cause of CVD-related health impairment worldwide impacts an individual's social, physical, economic, and psychological well-being significantly. Socioeconomic factors such as poverty, inflation, and literacy rates can impact individual experiences of Myocardial infarction (MI). Given the limited awareness and facilities in smaller regions of Pakistan, this study aims to explore the lived experiences of individuals following MI, in a district general hospital in Pakistan covering a large geographical area. METHODS: The study was conducted in a one-to-one interview fashion at a cardiology outpatient clinic in a remote region of Punjab, where people from all over Pakistan attend. To help guide the interviews, a questionnaire was designed. Interview questions were asked using a funnelled approach–starting with a general subject and progressing to more focused inquiries. The questionnaire consisted of six open-ended questions, followed by additional questions, specifically structured to elicit detailed responses regarding patients' experiences post-MI diagnosis. For data analysis, each statement was carefully coded, and sub-themes were identified using similar coded statements. Then, after a thorough assessment of data integrity, pertinent themes were identified to create distinct themes, which were then combined into groups. These themes were classified into physical, psychological and social impacts. RESULTS: 51 patients (34 men, 17 women) aged 37-86 years were interviewed. Analysis of interviews revealed both positive and negative biopsychosocial effects following diagnosis and treatment. Table 1 illustrates the major themes identified. Physically, participants reported improved chest symptoms and a partial return to routine activities but also reduced physical activity and weakness. Psychologically, experiences ranged from increased lifestyle modification to anxiety and persistent low mood. Lifestyle changes like dietary modifications and exercise were common, but negative impacts included loss of employment and reduced social contact. CONCLUSION: The findings of this study highlight the multifaceted impact of MI and underscore the need for comprehensive care plans by healthcare professionals in developing countries like Pakistan, delineating the need to incorporate physical rehabilitation, psychological support, and social engagement. Further research should delve deeper into these changes to formulate optimal post-MI care.